PENGARUH GROSS PROFIT MARGIN, NET PROFIT MARGIN DAN PERTUMBUHAN PENJUALAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Jessi Charina Sembiring; Wilsa Road Betterman Sitepu; Ninta Katharina; Lara Asmara; Tetty Tiurma Uli Sipahutar (Akuntansi Prima, 2023)
This research is aimed at determining the influence of Gross Profit Margin, Net Profit Margin, and Sales Growth on Profit Growth (in Manufacturing Companies listed on the IDX in 2019-2023). The data used is Secondary Data and the sampling method is purposive sampling, namely carrying out the best assessment to fulfill what has been determined with a sample of 11 companies for 5 years. The research approach uses a quantitative assessment approach. The technique used in the research is a multiple linear analysis technique using the SPSS 26 application. The research results show that gross profit margin, net profit margin, and sales growth have a simultaneous and significant effect on profit growth (in manufacturing companies listed on the BEI in 2019-2023) . Gross Profit Margin partially influences Profit Growth (in manufacturing companies listed on the IDX in 2019-2023). Net Profit Margin has a partial effect on profit growth (in manufacturing companies listed on the BEI in 2019-2023) and sales growth has a partial effect on profit growth (in manufacturing companies listed on the BEI in 2019-2023) Keywords: Gross Profit Margin, Net Profit Margin, Sales Growth, Profit Growth